Triterpenes from Momordica balsamina (African pumpkin): ABCB1 inhibition and synergistic interaction with doxorubicin in resistant cancer cells. (November 2022) - Silva, Cristina Duarte; Ramalhete, Cátia; Spengler, Gabriella; Mulhovo, Silva; Molnar, Joseph; Ferreira, Maria-José U.
Abstract: Aiming at overcoming multidrug resistance (MDR) in cancer, we have been studying Momordica balsamina, a vegetable known as African pumpkin . Five undescribed cucurbitane-type triterpenoids (balsaminaepoxide, balsaminatriol, balsaminoic acid, balsaminal, and balsaminol G) along with five known cucurbitacins were isolated from the methanol extract of Momordica balsamina aerial parts, whose structures were elucidated by spectroscopic data, mainly 1D and 2D NMR experiments. Compounds were evaluated for their ability as P-glycoprotein (P-gp/ABCB1) inhibitors in multidrug resistant human ABCB1 -transfected mouse lymphoma cells (L5178Y, MDR) and resistant human colon adenocarcinoma cells (COLO 320), using the rhodamine-123 exclusion test, by flow cytometry. Several compounds, which were found to be non-cytotoxic, strongly inhibited P-gp efflux activity in a dose-dependent manner in both cell models. In MRD mouse lymphoma cells, balsaminol G and karavilagenin B were the most active, while in resistant colon adenocarcinoma cells, the strongest inhibitory activity was found for balsaminaepoxide, balsaminatriol and karavilagenin C, being several-fold more active than the positive control verapamil. In chemosensitivity assays, in a model of combination chemotherapy, selected compounds showed to interact synergistically with doxorubicin, thus substantiating their potential as MDR reversers. The strongest synergistic interaction was found for balsaminal and balsaminol G. Graphical abstract: Five undescribed cucurbitane-type triterpenoids along with five known cucurbitacins were isolated from Momordica balsamina. Some compounds strongly inhibited P-gp efflux activity and interacted synergistically with doxorubicin. Image 1 Highlights: Ten cucurbitacins, including five undescribed, were isolated from Momordica balsamina . Their structures were elucidated mainly by 1D and 2D NMR experiments. They were evaluated as MDR reversers, by transport and chemosensitivity assays. Some compounds strongly inhibited P-gp efflux activity, in a dose-dependent manner. Selected compounds interacted synergistically with the anticancer drug doxorubicin.